Herbal Extracts: Importance, Classification, Quality Characteristics, and Control - Bien, Tran Trong; Tuyet, Tran Thi; Phuong, Bui Thi Lan; Van, Pham Thai Ha (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2022)
Herbal extracts are one of the herbal preparations obtained by the extraction method. There has been an increasing trend of application of herbal extracts to replace traditional medicinal herbs in using and manufacturing of drug dosage forms. The quality characteristics of herbal extracts roots from their multi-components nature, leading to multiple targets and mechanisms of action. Thus hindering the development of quality assessment systems and also the application of pharmaceutical technologies in the development of modern dosage forms, leading to a decrease in therapeutic efficacy in clinical practice. This review systematizes some information related to herbal extracts: the position and importance of herbal extracts in drug research and development, classification, characteristics, and quality control strategies. The purpose of this review is to consolidate and expand the general understanding of the “pharmaceutical nature” of herbal extracts and to provide some quality control strategies using markers and reference materials Keywords Herbal extracts, quality characteristics, classification, quality control, pharmaceutical nature.